From telescope to binoculars. Dyadic outcome resulting from psychological counselling for infertile couples undergoing ART. (1st January 2019) - Donarelli, Zaira; Salerno, Laura; Lo Coco, Gianluca; Allegra, Adolfo; Marino, Angelo; Kivlighan, Dennis M.
ABSTRACT: Objective : This longitudinal study aims to evaluate the effect of psychological counselling on quality of life, marital satisfaction and need for parenthood in couples undergoing fertility treatments (ART). Background : Recent guidelines on the ART suggest that psychological counselling should target both members of the infertile couple in order to improve their conjoint management of the infertility-related stress. However, studies on the dyadic outcome of couples are scarce. Methods : 262 patients were originally considered in the study and completed questionnaires on quality of life, need for parenthood and marital satisfaction, before treatment (T1) and at the day of intrauterine insemination/embryo transfer (T2). For the purposes of this study, 34 counselled couples were then matched to 34 non-counselled couples by propensity scores. The Common Fate Model (CFM) was used to examine dyadic changes. Results : Couples receiving counselling had higher dyadic quality of life and lower dyadic stress due to the need for parenthood at T2 compared to non-counselled couples. No differences were found on marital satisfaction. Conclusion : The findings provide support for the effectiveness of counselling on interpersonal outcome. The CFM allows researchers to examine how the dyad as a whole responds to counselling, highlighting the change in the couple's relational dynamics.